Study of Z boson plus jets events using variables sensitive to double-parton scattering in pp collisions at 13 TeV - Tumasyan, A. (2021)
Double-parton scattering is investigated using events with a Z boson and jets. The Z boson is reconstructed using only the dimuon channel. The measurements are performed with proton-proton collision data recorded by the CMS experiment at the LHC at s = 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1 collected in the year 2016. Differential cross sections of Z+ ≥1 jet and Z+ ≥2 jets are measured with transverse momentum of the jets above 20 GeV and pseudorapidity |η| < 2.4. Several distributions with sensitivity to double-parton scattering effects are measured as functions of the angle and the transverse momentum imbalance between the Z boson and the jets. The measured distributions are compared with predictions from several event generators with different hadronization models and different parameter settings for multiparton interactions. The measured distributions show a dependence on the hadronization and multiparton interaction simulation parameters, and are important input for future improvements of the simulations. [Figure not available: see fulltext.]